Controlled prospective neuropsychological assessment of active experienced amateur boxers - Porter, M. D.; Fricker, P. A. (Clinical Journal of Sport Medicine, 1996)
OBJECTIVE. To use a practical battery of eight neuropsychological tests for the detection of an association between amateur boxing and chronic traumatic encephalopathy. DESIGN. A controlled prospective neuropsychological study over a 15-18-month period. SETTING. Dublin, Ireland. March 1992 to September 1993. PARTICIPANTS. Twenty experienced actively competing amateur boxers and 20 controls matched for age and socioeconomic status. INTERVENTIONS. Participation in competitive amateur boxing and training. MAIN OUTCOME MEASURES. Absolute scores, and changes in scores, in the neuropsychological tests. RESULTS. At the end of the study period, the boxers performed significantly better then the controls in both the Trail-Making Tests A and B (TMT-A, TMT-B), whereas the control group's scores for the Finger Tapping Tests (FTT) were significantly higher than those of the boxers. The boxer's scores for the dominant-hand FTT showed a significant deterioration, but there was no association between this change and boxing exposure. CONCLUSIONS. There was no evidence of neuropsychological impairment in the boxers as compared with socioeconomically, educationally and age-matched controls, and there was no association between boxing exposure and performances in any of the neuropsychological tests used. There is accumulating evidence that amateur boxing is not associated with chronic traumatic encephalopathy but longer term prospective studies are needed.